2011
DOI: 10.1007/s11916-011-0242-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Challenges and Interventional Pain Medicine

Abstract: The relief of suffering and the cure of disease must be seen as twin obligations of a medical profession that is truly dedicated to the care of the sick. Physicians' failure to understand the nature of suffering can result in medical intervention that (though technically adequate) not only fails to relieve suffering but becomes a source of suffering itself." -Eric J. Cassel [1] We must abandon those orientations that treat pain as an object independently of the being that it affects. -Giordano and Schatman [2]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…In the present study, patients with FM reported higher ratings in response to single and repeated IES, but temporal summation of pain was not significantly different from that observed in HC subjects. This is consistent with several other studies which showed that patients with FM were not significantly different from HC subjects when testing temporal summation of pain using pinprick [ 4 , 74 , 75 ] or thermal stimuli [ 30 ], or when testing reflex responses to nociceptive electrical stimulation [ 29 ]. In contrast, several other studies have reported increased temporal summation of pain in response to thermal stimuli [ 10 , 11 ], and reduced reflex responses to nociceptive electrical stimulation in patients with FM [ 6 , 76 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, patients with FM reported higher ratings in response to single and repeated IES, but temporal summation of pain was not significantly different from that observed in HC subjects. This is consistent with several other studies which showed that patients with FM were not significantly different from HC subjects when testing temporal summation of pain using pinprick [ 4 , 74 , 75 ] or thermal stimuli [ 30 ], or when testing reflex responses to nociceptive electrical stimulation [ 29 ]. In contrast, several other studies have reported increased temporal summation of pain in response to thermal stimuli [ 10 , 11 ], and reduced reflex responses to nociceptive electrical stimulation in patients with FM [ 6 , 76 ].…”
Section: Discussionsupporting
confidence: 92%
“…Trescot and Cohen refreshingly address the imperatives of cost utility and put the patient's well‐being ahead of issues of remuneration. This is encouraging, particularly given the criticism in the recent literature regarding the mercenary practice patterns of some interventionalists in the face of questionable evidence basis [1,2]. Although some would question the ethics of placing financial limitations on pain relief, Dr. Cohen notes that we live in an imperfect world, and physicians must become progressively cognizant of cost‐effectiveness.…”
mentioning
confidence: 99%